MENIMBANG HERMENEUTIKA DEKONSTRUKSI IBN ‘ARABI - Tri Utami Oktafiani; Muhammad Minanur Rohman (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2020)
This research discusses how Ibn ‘Arabi deconstructed masculine linguistic structure that having been firmly entrenched in religious traditions. For Ibn Arabi, religious conversation is no more than a discourse that tends to be masculine. Ibn ‘Arabi tried to present a deconstructing of linguistic structure, namely by making femininity as the starting point for religious discourse. The material object of this research is the thought of Ibn ‘Arabi. The formal object is the deconstructive feminist criticism Hélène Cixous. By tracing the theological motives of structural-linguistic deconstruction in Ibn ‘Arabi thought, this study aims to explore the relevance of structural-linguistic deconstruction in the context of religious discourse.